Preservation and conservation of Islamic manuscript in global context - a review on Islamic Manuscript Association policy and projects - Barkeshli, Mandana (2013)
Preservation and conservation of Islamic manuscripts is a global concern due to its urgent need for its care and accessibility. In the present paper the author is highlighting the effort that is done by the Islamic Manuscript Association towards this need in global context. This includes an introduction to the association’s aims and vision, organisational chart, its activities and the funds and is granted yearly for preservation of Islamic manuscripts. More over sincethe author has been the board member of the association for six years and one of the team members of the conservation panel of Islamic Manuscript Association till present in this paper she will try to highlight the projects that specifically have been developed during last few years in conservation and preservation area related to Islamic manuscript. Among them the recent project that jointly has been carried out under Research Matching Grant Study between Islamic Manuscript Association and International Islamic University Malaysia will be introduced and explained.